Electrical and Dielectric properties of 3, 3’, 3’’, 3’’’-tetra poly (1, 4-diaminobenzen phthalate) phthalocyanine copper (II) thin films prepared by casting method. - Falak, Ziyad (University of Thi-Qar Journal of Science, 2019)
In this study, 3, 3’, 3’’, 3’’’-tetra poly (1, 4-diaminobenzen phthalate) phthalocyanine copper (II) film was prepared by casting method. The study consists of two parts: the first includes the measurement of electrical conductivity and activation energy range (303-353) °K. The second part deals with the dielectric properties that were measured at temperatures ranging from 303 to 353°K and frequency in the range (120Hz - 2MHz). Dielectric properties (dielectric permittivity, loss tangent and Ac. conductivity (σac) have also been investigated. It is found that the system obeys the Maxwell-Wagner Sillars relaxation of space charge phenomenon. Permittivity, loss tangent and Ac. conductivity increase with increasing the temperature and the permittivity decreases with the increasing of frequency. The values of ac conductivity and dc conductivity were compared.